2019
DOI: 10.3390/nu11092120
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Supplementation Improves Anaerobic Performance and Neuromuscular Efficiency and Fatigue in Olympic-Level Boxers

Abstract: Background: this study examined the effects of caffeine supplementation on anaerobic performance, neuromuscular efficiency and upper and lower extremities fatigue in Olympic-level boxers. Methods: Eight male athletes, members of the Spanish National Olympic Team, were enrolled in the study. In a randomized double-blind, placebo-controlled, counterbalanced, crossover design, the athletes completed 2 test sessions after the intake of caffeine (6 mg·kg−1) or placebo. Sessions involved initial measures of lactate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 62 publications
3
43
0
2
Order By: Relevance
“…The purpose of this investigation was to determine the effects of acute caffeine supplementation on CrossFit ® performance and perceptual responses to exercise in CrossFit ® -trained men. Because of the well-documented ergogenic effects of caffeine that are likely due to central mechanisms [2,3,5,42], it was hypothesized that caffeine supplementation would improve CrossFit ® performance. The hypothesis was not supported, as no significant improvement in CrossFit ® performance or perceptual responses was found after caffeine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this investigation was to determine the effects of acute caffeine supplementation on CrossFit ® performance and perceptual responses to exercise in CrossFit ® -trained men. Because of the well-documented ergogenic effects of caffeine that are likely due to central mechanisms [2,3,5,42], it was hypothesized that caffeine supplementation would improve CrossFit ® performance. The hypothesis was not supported, as no significant improvement in CrossFit ® performance or perceptual responses was found after caffeine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the effectiveness of caffeine supplementation on sports performance in which aerobic [1], anaerobic [2,3,4] or mixed [5,6,7] metabolism is prioritized. Current guidelines recommend the ingestion of low-to-moderate doses of caffeine, ranging from 3 to 6 mg/kg, approximately 60 min prior to exercise to get these improvements [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, examining the effect of caffeine supplementation on repeated bouts of Wingate tests (four 30-s Wingate tests with 4 min of rest between each exercise) after caffeine (6 mg∙kg − 1 ) or placebo ingestion, Greer, McLean, and Graham (1998) observed that caffeine ingestion had an ergolytic effect in the latter two exercise bouts [ 48 ]. Otherwise, it was recently reported that caffeine supplementation (6 mg∙kg − 1 ) increased the peak power during Wingate anaerobic test and diminished neuromuscular fatigue, shown by attenuation of decrease in countermovement jump performance after Wingate test [ 55 ] . Thus, since increase [ 55 , 56 ] and reduction [ 48 , 57 ] of different markers of exercise tolerance after caffeine supplementation already been reported, the recommendation of caffeine supplementation to improve recreational or athletic performance should be made cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, it was recently reported that caffeine supplementation (6 mg∙kg − 1 ) increased the peak power during Wingate anaerobic test and diminished neuromuscular fatigue, shown by attenuation of decrease in countermovement jump performance after Wingate test [ 55 ] . Thus, since increase [ 55 , 56 ] and reduction [ 48 , 57 ] of different markers of exercise tolerance after caffeine supplementation already been reported, the recommendation of caffeine supplementation to improve recreational or athletic performance should be made cautiously.…”
Section: Discussionmentioning
confidence: 99%